Donation-Based Crowdfunding: Systematic Literature Review - Aimi Fadzirul Kamarubahrin; Rafisah Mat Radzi; Nurul Aini Muhamed; Wan Nur Fazni Wan Mohamad Nazarie; Muhammad Iqmal Hisham Kamaruddin (IIUM Press, 2024)
This study uses a systematic review to discover, analyses, and summarize donation-based crowdfunding. The related literature was subjected to a systematic literature review (SLR) for the current paper. By searching electronic open-access databases like Google Scholar, Scopus, and Emerald Insights, a systematic review of the literature was able to be conducted. A publication date between 2018 and 2022, a country, a methodology, and a dimension were the inclusion criteria. Using the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) search methodology strategy, a narrative synthesis and systematic review were carried out and reported in accordance with the preferred reporting items statement. 409 studies from different sources have been found through a systematic review of the literature. 30 studies have been determined to be pertinent to the current study after the 379 studies were eliminated based on the selection criteria. According to the review, donation-based crowdfunding is essential to advance the development and raise awareness of those who cannot obtain loans. The study develops a research model that policymakers can use to develop a crowdfunding platform appropriately. The platform will help the country's economy grow thanks to improved performance and better financial access. This study proposes a one-of-a-kind research model to demonstrate donation-based crowdfunding.